Influence of Renin-Angiotensin System Inhibitors on Postoperative Delirium in Patients With Pulmonary Arterial Hypertension: A Secondary Analysis of a Retrospective Cohort Study - Chen, Gong; Zhou, Sai; Deng, Fang (Frontiers in Psychiatry, 2022)
Objective To investigate the correlation between preoperative use of ACEIs/ARBs and postoperative delirium (POD) in surgical patients with pulmonary arterial hypertension (PAH). Methods The present study is a secondary analysis of a retrospective cohort study conducted at the University of Washington Medical Center from April 2007 to September 2013. Patients with PAH who underwent non-cardiac, non-obstetric surgery were enrolled in the original research. We further excluded stroke, sepsis, and craniotomy patients from interfering with POD evaluation. The univariate regression analysis and multivariate-adjusted model were used to explore the influence of preoperative ACEIs/ARBs use on the occurrence of POD. Results A total of 539 patients were included in this study. The incidence of POD in these patients was 3.0%. Following the adjustment of potential confounders (age, BMI, smoking status, pulmonary arterial systolic pressure, length of surgery, vascular surgery, asthma, obstructive sleep apnea, renal failure, atrial fibrillation, coronary artery disease, hydrochlorothiazide, alpha-blocker, calcium channel blocker, antiplatelet, steroids, statin, isoflurane), a negative relationship was found between preoperative use of ACEIs/ARBs and occurrence of POD (OR = 0.15, 95%CI: 0.03 to 0.80, P = 0.0266). Conclusion Preoperative use of ACEIs/ARBs in patients with PAH reduces the risk of POD. ACEIs/ARBs may be more recommended for patients with PAH in the future.